Development of Virtual i-Learn Community 2: u-learn / Nurhamizah Mohd Hasnan - Mohd Hasnan, Nurhamizah (2013)
Virtual i-Learn Community (VIC) is enhancement from i-Learn. i-Learn is a Learning Management System (LMS) that has adopted to enhance online student learning and collaboration. Virtual i-Learn Community is focus on development of server, isometric avatar based system client, chatting and announcement module. But VIC was not deploying due to the limited technological features available in that system. VIC also has no useful and knowledgeable function for students and lecturers. Based on that fact, it is attention the university to design and develop u-Learn system to create a platform that focus on interaction and communication between user to support teaching and learning. The u-Learn system that contain the features that allows Massive Multiplayer Online Chat Community (MMOCC) modules which are available all around the globe in a classroom environment through the use of avatar that can be control by multiple user at one time. As the result, this u-Learn will optimize the use of physical lab and improve online teaching and learning for FSKM students and lecturers.